Tinjauan Yuridis terhadap Peredaran Produk Kosmetik Ilegal - Liandhajani Liandhajani (LITERATUS, 2022)
This research is descriptive analytical which describes the data. The instruments of this study were obtained through observations, interviews, documents, and field notes. This study uses a normative-based legal methodology. Where in this study using literature studies (secondary sources) or legal literature studies which are generally intended to examine legal concepts and legal systematics. Data. Primary obtained through field work. Secondary data comes from laws and regulations, regulations, textbooks, and data from other institutions or institutions related to the title of this research. This type of research is normative juridical. The object of this research is BPOM (Food and Drug Supervisory Agency) and cosmetic users. The results of this study are (1) the formulation of the right rules to eradicate illegal cosmetic producers, making legislation in full and not separated so as to facilitate the understanding of business actors and consumers (2) Measures to prevent the circulation of illegal cosmetics This can be prevented by continuous socialization to the public and education of applicable regulations and legal sanctions if violated.